2015 IEEE International Symposium on Information Theory (ISIT) 2015
DOI: 10.1109/isit.2015.7282903
|View full text |Cite
|
Sign up to set email alerts
|

Lattice index codes from algebraic number fields

Abstract: Broadcasting K independent messages to multiple users where each user demands all the messages and has a subset of the messages as side information is studied. Recently, Natarajan, Hong, and Viterbo proposed a novel broadcasting strategy called lattice index coding which uses lattices constructed over some principal ideal domains (PIDs) for transmission and showed that this scheme provides uniform side information gains. In this paper, we generalize this strategy to general rings of algebraic integers of numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…In this way, the D 4 lattice is partitioned into 25 cosets. Even though H is a PID [36], we only have the group homomorphism as the multiplication for H is non-commutative. Now we compare the mutual information of the D 4 lattice with that of a two-dimensional lattice to see the performance gain introduced by the multi-dimensional lattices.…”
Section: A Ira Lattices Constructionmentioning
confidence: 99%
“…In this way, the D 4 lattice is partitioned into 25 cosets. Even though H is a PID [36], we only have the group homomorphism as the multiplication for H is non-commutative. Now we compare the mutual information of the D 4 lattice with that of a two-dimensional lattice to see the performance gain introduced by the multi-dimensional lattices.…”
Section: A Ira Lattices Constructionmentioning
confidence: 99%
“…In [17], Huang considers the same multicasting problem with message side information, where each link experiences a Rayleigh fading channel on top of the AWGN noise. It is well-known that in contrast to the AWGN channel, maximizing minimum distance alone is far from enough for the Rayleigh fading channel and the minimum product distance dominates the performance [19]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that in contrast to the AWGN channel, maximizing minimum distance alone is far from enough for the Rayleigh fading channel and the minimum product distance dominates the performance [19]- [21]. The lattice index coding scheme proposed in [17] generalizes the idea of [16] from some famous principal ideal domains to any ring of algebraic integers. It is shown that codes thus constructed over rings of algebraic integers of totally real number fields provide gains in minimum product distance that is exponential with the rate of the side information for any index set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6], the same problem was studied for the Rayleigh fading channel in which the minimum product distance is much more important than the minimum Euclidean distance. The new lattice index code construction for the Rayleigh fading channel in [6] provides exponentially increased squared minimum product distance as the rate of side information increases and provides uniform side information gain for any side information configuration.…”
Section: Introductionmentioning
confidence: 99%